COMPARISON OF MORAL ASSESSMENT OF SPECIAL AND REGULAR PROGRAM STUDENTS IN LEARNING MORAL CREED The MTSN2 Surakarta - Kusuma, Ria Nata; Anshori, Ari (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This study focuses on the comparison of student behavior and teaching approaches between students who attend special class programs and regular class students at the secondary school level. This research was conducted in the context of Islamic religious education with the aim of evaluating the teaching of moral creed subjects. This type of research uses qualitative methodology. Participants in the study involved 60 students who were divided into two class categories, namely special program classes numbering 28 and regular classes numbering 32 in class VIII. As well as teachers who teach moral creed subjects. Data collection is carried out through observation, interviews, and document collection, with an analytical approach that emphasizes qualitative description and understanding. The results showed from the regular class that from the data obtained there was a comparison with the first indicator regarding cooperation in kindness seen from the regular class score obtained 2,732, an average of 85.37 and a percentage of 85%, the second indicator did not demean people with a score of 2,677, an average of 83.65 and a percentage of 83%, and the third indicator of forgiving others with a score of 2,678, average 83.68 and percentage 83%. The comparison in the special program class in the first indicator regarding cooperation in kindness can be seen from the score obtained 2,577, an average of 92.03 and a percentage of 92%, the second indicator does not underestimate people with a score of 2,432, an average of 86.85 and a percentage of 87%, and the third indicator of forgiving others with a score of 2,568, an average of 91.71 and a percentage of 91%. Special program classes have a better impact than regular classes, but the overall moral assessment of students still shows a good level.